2016
DOI: 10.1017/s1474746416000579
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Abuse and Harassment: The Vulnerability of Informal and Migrant Domestic Workers in Portugal

Abstract: Policy makers and researchers are alarmed by the pervasive substandard working conditions and mistreatment in domestic work worldwide. Using an original dataset from a sample of domestic workers in Portugal (n=684), our study explores types of abuse and harassment and tries to unveil the potential factors affecting the likelihood of having been a victim. Empirical evidence pointed to three segments of domestic workers: victims of labour abuses related to contract and wages, victims of multiple abuses including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 41 publications
1
13
1
1
Order By: Relevance
“…They suffer due to the oppressive neocolonial logics of exploitation and abuse that shape interactions in such private space [41]. Participants in this study reported often having experienced discrimination in forms of abuse, such as delayed payment, withholding food or sexual harassment, coinciding with a similar study in Portugal [74]. In addition, Latin American housekeepers in hotels are also vulnerable to abuses including disrespect, unfair job demands, and verbal abuse by managers [75].…”
Section: Discussionsupporting
confidence: 60%
“…They suffer due to the oppressive neocolonial logics of exploitation and abuse that shape interactions in such private space [41]. Participants in this study reported often having experienced discrimination in forms of abuse, such as delayed payment, withholding food or sexual harassment, coinciding with a similar study in Portugal [74]. In addition, Latin American housekeepers in hotels are also vulnerable to abuses including disrespect, unfair job demands, and verbal abuse by managers [75].…”
Section: Discussionsupporting
confidence: 60%
“…For example, a qualitative study of Latina hotel workers reports that immigrants were vulnerable to disrespect, unfair work assignments, and verbal abuse from managers (45). In Portugal, migrant domestic workers often experienced workplace abuses, including delayed payment, sexual harassment, withholding of food, and discrimination (27).…”
Section: Working Conditionsmentioning
confidence: 99%
“…The Human Rights Watch, among others, has reported on domestic workers' exploitative working conditions, with excessively long and often unpaid hours of work, restrictions on freedom of movement, and contact with others [4,5] in what Jureidini and Moukarbel aptly describe as "contract slavery" [6]. In the literature, authors have reported on the increased risk for abuse faced by domestic workers (e.g., [7][8][9]), whilst the sexualised nature of domestic work, the heightened power imbalance between employer and employee, and the confinement of work within the private sphere places women at particular risk for workplace sexual harassment and assaults [10][11][12]. A high incidence of sexual harassment is reported among domestic workers, especially those living in their employer's residence [11].…”
Section: Introductionmentioning
confidence: 99%